2015
DOI: 10.1186/s12937-015-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral consumption of α-linolenic acid increases serum BDNF levels in healthy adult humans

Abstract: Background aimsDietary omega-6 and omega-3 fatty acids have remarkable impacts on the levels of DHA in the brain and retina. Low levels of DHA in plasma and blood hamper visual and neural development in children and cause dementia and cognitive decline in adults. The level of brain-derived neurotrophic factors (BDNF) changes with dietary omega-3 fatty acid intake. BDNF is known for its effects on promoting neurogenesis and neuronal survival.MethodsIn this study, we examined the effect of the oral consumption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…While the clinical improvement was supported by the enhancements in the serological data, no neurological mechanism of action was established in the study. Additionally, animal studies and at least one human study have shown that many of the nutrients in APMC, including polysaccharides, antioxidants, resveratrol, and omega-3 fatty acids, have individual benefits on cognition and memory [17][18][19][20][21] and can increase BDNF levels [22][23][24][25]. The sum of these findings suggests that long-term oral supplementation can modulate BDNF production in the brain and can also explain the memory improvements demonstrated in our prior studies.…”
Section: Journal Of Clinical and Translational Researchsupporting
confidence: 57%
“…While the clinical improvement was supported by the enhancements in the serological data, no neurological mechanism of action was established in the study. Additionally, animal studies and at least one human study have shown that many of the nutrients in APMC, including polysaccharides, antioxidants, resveratrol, and omega-3 fatty acids, have individual benefits on cognition and memory [17][18][19][20][21] and can increase BDNF levels [22][23][24][25]. The sum of these findings suggests that long-term oral supplementation can modulate BDNF production in the brain and can also explain the memory improvements demonstrated in our prior studies.…”
Section: Journal Of Clinical and Translational Researchsupporting
confidence: 57%
“…On the contrary, a weekly oral assumption of α-linoleic acid increased plasma BDNF levels, particularly in women (195). OGTT-induced hyperglycemia also decreased plasma but not serum BDNF and return to baseline was faster in normoglycemic subjects than in borderline/diabetic ones (190).…”
Section: Pre-analytical Factorsmentioning
confidence: 85%
“…Thus, it may be effective to treat depression through these pathways, as the results of the present study are also consistent with these earlier findings. [38] The beneficial effect of ALA on depressive symptoms has previously been shown in a study on mice. The result of this study revealed that ALA treatment on mice led to decreased depressive behavior, in comparison with vehicle-treated mice, as well as being effective in compensating for or repairing neural plasticity.…”
Section: Discussionmentioning
confidence: 83%